2019
DOI: 10.1136/thoraxjnl-2018-212340
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic genotypes and risk of severe exacerbations in COPD: a prospective cohort study

Abstract: BackgroundIndividual susceptibility to exacerbations in chronic obstructive pulmonary disease (COPD) is likely influenced by genetic factors; however, most such variance is unexplained. We hypothesised that β2-adrenergic receptor genotypes, Gly16Arg (rs1042713, c.46G>A) and Gln27Glu (rs1042714, c.79C>G) influence risk of severe exacerbations in COPD.MethodsAmong 96 762 individuals in the Copenhagen General Population Study, we identified 5262 with COPD (forced expiratory volume in one second divided by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…The results of the study showed an increased risk of COPD exacerbations in carriers of Arg16 and Gln27 [20]. However, the proportion of COPD patients treated with LABA from the Copenhagen General Population Study was low (9.8%) [20] particularly in comparison to our finding that revealed a protective effect in the category of current users of inhaled β 2 -agonists. So far, a few studies have examined the association between ADRB2 haplotypes and response to β 2 -agonist [9,21,23].…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The results of the study showed an increased risk of COPD exacerbations in carriers of Arg16 and Gln27 [20]. However, the proportion of COPD patients treated with LABA from the Copenhagen General Population Study was low (9.8%) [20] particularly in comparison to our finding that revealed a protective effect in the category of current users of inhaled β 2 -agonists. So far, a few studies have examined the association between ADRB2 haplotypes and response to β 2 -agonist [9,21,23].…”
Section: Discussioncontrasting
confidence: 71%
“…A recent observational study, in spirometry-confirmed COPD patients, examined the associations between ADRB2 polymorphisms (Arg16Gly and Gln27Glu) and risk of severe COPD exacerbations. [20]. The results of the study showed an increased risk of COPD exacerbations in carriers of Arg16 and Gln27 [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Thorax , using data from individuals with COPD in the Copenhagen General Population Study (n=5,262) and the Copenhagen City Heart Study (n=923), Ingebrigtsen et al tested the association of β2 adrenergic receptor polymorphisms Gly16Arg (rs1042713, c.46G>A) and Gln27Glu (rs1042714, c.79C>G) with incident risk of COPD exacerbations requiring hospitalization 10 . In the Copenhagen General Population Study, compared to 16Gly homozygotes, 16Gly/Arg heterozygotes (hazards ratio [HR] 1.62, 95% confidence intervals [CI] 1.30-2.03, p=0.00002) and 16Arg homozygotes (HR 1.41, 95% CI 1.04-1.91, p=0.03) were more likely to experience severe COPD exacerbations.…”
mentioning
confidence: 99%
“…Furthermore, the findings of this study could potentially impact a large number of individuals with COPD given the high prevalence of the studied β2 adrenergic receptor polymorphisms. For comparison, while it is estimated that fewer than 10% of COPD patients carry the Pi*Z allele variant in the SERPINA1 gene associated with alpha-1 anti-trypsin deficiency 12 , more than 60% are carriers of the 16Arg allele in rs1042713 810 .…”
mentioning
confidence: 99%